Investigating High School Students’ Perceptions on The English Teacher’s Use of Project-Based Learning in Teaching Reading Comprehension - Hadi, Moch. Rizky Oktavian; Sundari, Siti; Tasnim, Zakiyah (English Education Study Program, 2023)
English is considered as the major foreign language to learn in Indonesia. English is mainly taught in Indonesian classrooms as a required subject, but it is not given as a daily communication language. Dealing with reading comprehension of English texts, English teachers seem to look for the most effective way to teach reading skill to get reading comprehension. One learning model that can be applied as an alternative for teaching reading comprehension is Project-Based Learning (PBL). This research used a qualitative descriptive approach. The data taken were interview of the students based on their experiences in dealing with Project-Based Learning (PBL). The results of thematic analysis showed: (1) The students’ perceptions on the English teacher’s overview in explaining the application of Project-Based Learning (PBL); (2) The students’ perceptions on the English teacher’s explanation about the meaning of Project-Based Learning (PBL); (3) The students’ perceptions on the implementation of Project-Based Learning (PBL) in the classroom; (4) The students’ perceptions on the benefit of using Project-Based Learning (PBL) in the classroom; (5) The students’ perceptions on the difficulty of doing Project-Based Learning (PBL) task. The research findings and discussion revealed that those five perceptions were the students’ perceptions.